Analisa Pengaruh Kepercayaan, Jaminan Rasa Aman, dan Aksesbilitas terhadap Minat Menabung Nasabah Bank Danamon di Surabaya - Yohana Neysa Setyawan (Jurnal Strategi Pemasaran, 2014)
Among the number of national banks, the biggest increasing for savings application for three years is Danamon Bank. During latest three years, the number of savings application at Danamon Bank more than 30%. The increasing of of savings application at Danamon Bank caused by consumer trust, safety guarantee, and accessibility. The purpose of this research is to identify terhadap impact of consumer trust, safety guarantee, and accessibility towards savings application at Danamon Bank.The research use causal design. The independent variables are: consumer trust, safety guarantee, and accescibility. While the dependent variable is savings application. The number of samples are 100 samples. Data analysis technique by linier double regression. The research showing that consumer trust, safety guarantee, and accescibility have impact toward savings application. As the conclusion, safety guarantee have biggest impact towards savings application.